Linguistic Environment – the Part of University Culture and the Educational Factor - Celiešienė, Vilija (Acta Paedagogica Vilnensia, 1998)
The linguistic environment of a university not only influences university culture and develops students’ language, it is closely connected with a personality’s intellectual, cultural and mental development. Besides the right language surrounding helps students in their information perception and speciality studies.